Analysis of the Impact of the Earthquake on the Economy of Wirotaman Village, Ampelgading District, Malang Regency - M. Rihal Irsyada; Sukron Rochmat Romadlon (International Journal of Economic Research and Financial Accounting, 2024)
The impact of an earthquake on the economic sector is very large. Mainly what happens in the economy of society with insufficient human resource capacity and invalid capital. This is like what happened in the 2021 Earthquake in Ampelgading District, Malang Regency. With the greatest damage impact occurring in Wirotaman Village. This research used qualitative descriptive methods with a research period of 3 months from 1 April - 1 July 2022. Data collection methods used interviews, observation and documentation techniques while the data analysis tool used was Multiple Linear Regression. The results of the research show that there is an impact due to the earthquake disaster on the economy of village communities. Because there is an obstacle in the production and distribution sectors. This results in widespread unemployment and poverty